Evaluation of the Effect of Cichorium intybus L. on the Liver Enzymes in Burn Patients: A Randomized Double-Blind Clinical Trial - Abdolkhalegh Keshavarzi; Rahimeh Akrami; Mohammad M. Zarshenas; Saeid Zareie; Tayyeb Ghadimi; Ali Najafi; Mahsa Rostami Chijan; Azizallah Dehghan; Elham Zarenezhad (International Journal of Clinical Practice)
Burn injuries are considered an important public health problem in the world. Burns are considered the fourth most common kind of trauma in the world, after traffic accidents, falls, and interpersonal violence. Various biochemical agents are involved in the burn healing process such as cytokines (such as IL-6 and TNF-α), antioxidants, and liver and kidney damage biomarkers. Cichorium intybus L. and milk thistle extracts showed a wide range of pharmacological activities such as significant antimicrobial effect and antioxidant activity, as well as anti-inflammatory, antidiabetic, antiproliferative, antiprotozoal, and hepatoprotective effect. Also, these two herbs possess blood-cleansing, detoxifying, laxative, and invigorating activities. Some research confirmed that the preparations of the extract are very suitable for the treatment of nonalcoholic fatty liver disease. This is a double-blind randomized controlled clinical trial. Patients with 2nd and 3rd degree burns have been selected to participate in the study according to the inclusion criteria. A total of 60 patients were selected and divided into intervention and control groups (30 patients in each group). Patients in the intervention group received chicory seed syrup 10 cc three times a day and 1 placebo capsule, and those in the control group received placebo syrup (10 cc three times a day) and one Livergol (140 mg of silymarin in each capsule) capsule. Lab data such as liver function tests, albumin, creatinine, BUN, and hemoglobin were checked every 3 days and 1 week after discharge. The treatment lasted for 4 weeks. According to the results of the study, although the average of liver enzymes at the end of the study does not show a significant difference between the two groups, the level of liver enzymes in each group decreased on the 15th day of the study compared to the first day. This trial is registered with IRCT20180609040016N1.